2020
DOI: 10.7759/cureus.9057
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Therapies in Sarcoidosis and Uveitis: A Review

Abstract: Sarcoidosis and uveitis are chronic inflammatory conditions with potentially debilitating effects on quality of life. Steroids form the mainstay standard therapy in both conditions. Biologic agents are considered to be appropriate alternatives for treatment in steroid-refractory sarcoidosis and uveitis due to the role of tumor necrosis factor (TNF) in mediating the inflammatory cascade seen in both conditions. We performed a thorough literature search using PubMed to compare the extent of use, efficacy, and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…135,136 Infliximab is similar to adalimumab in treatment response and safety. 137,138 Both infliximab and adalimumab have demonstrated success in patients with refractory chronic sarcoid uveitis that has failed to respond to at least one conventional immunosuppressive medication, resulting in improvement in inflammation including anterior chamber cell, vitreous haze, central macular thickness and reduction in corticosteroid dosing. 139,140 In rare cases, refractory to third-line therapy, rituximab and newer biologics including tocilizumab and Janus kinase (JAK) inhibitors, may be effective.…”
Section: Systemic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…135,136 Infliximab is similar to adalimumab in treatment response and safety. 137,138 Both infliximab and adalimumab have demonstrated success in patients with refractory chronic sarcoid uveitis that has failed to respond to at least one conventional immunosuppressive medication, resulting in improvement in inflammation including anterior chamber cell, vitreous haze, central macular thickness and reduction in corticosteroid dosing. 139,140 In rare cases, refractory to third-line therapy, rituximab and newer biologics including tocilizumab and Janus kinase (JAK) inhibitors, may be effective.…”
Section: Systemic Treatmentmentioning
confidence: 99%
“…Data from clinical trials have shown good effect with adalimumab for non‐infectious uveitis leading to significant reduction in risk of treatment failure and achieving steroid‐free disease quiescence 135,136 . Infliximab is similar to adalimumab in treatment response and safety 137,138 . Both infliximab and adalimumab have demonstrated success in patients with refractory chronic sarcoid uveitis that has failed to respond to at least one conventional immunosuppressive medication, resulting in improvement in inflammation including anterior chamber cell, vitreous haze, central macular thickness and reduction in corticosteroid dosing 139,140 …”
Section: Treatmentmentioning
confidence: 99%
“…Moreover, monoclonal antibodies like infliximab, adalimumab, rituximab, and golimumab which are mostly prescribed to treat overactive immune systems may also be the drug of choice in many cases where a specific antibody is required to treat a specific antigen. Infliximab has been studied in randomized controlled trials and reported to possess beneficial effects on both pulmonary and extra-pulmonary sarcoidosis in a subgroup of carefully selected patients 38,39,40 .…”
Section: Fig 2: Structures Of Drugs Prescribed For Sarcoidosismentioning
confidence: 99%
“…This medicine is the first-line treatment in gout to treat joint pain associated with sarcoidosis. The major adverse effects related to the use of this drug are nausea, vomiting, diarrhea, and stomach cramps or pain 38 . CONCLUSION: However, sarcoidosis is a rare autoimmune inflammatory disease; an improvement in the cases of sarcoidosis has been seen in recent years, much research is unknown and going on.…”
Section: Fig 2: Structures Of Drugs Prescribed For Sarcoidosismentioning
confidence: 99%